2014
DOI: 10.1016/j.physb.2014.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical response of ultracold interacting fermion–boson mixtures

Abstract: We analyze the dynamical response of a ultracold binary gas mixture in presence of strong boson-fermion couplings. Mapping the problem onto that of the optical response of a metal/semiconductor electronic degrees of freedom to electromagnetic perturbation we calculate the corresponding dynamic linear response susceptibility in the non-perturbative regimes of strong bosonfermion coupling using diagrammatic resummation technique as well as quantum Monte Carlo simulations. We evaluate the Bragg spectral function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 35 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…(27). In an earlier work [44], we have studied the fermion-phonon correlation in Bragg spectra by a random phase approximation (RPA). That formalism has an advantage to reveal the interaction effects in a simple way.…”
Section: Sws In Fermion-boson Mixturesmentioning
confidence: 99%
See 4 more Smart Citations
“…(27). In an earlier work [44], we have studied the fermion-phonon correlation in Bragg spectra by a random phase approximation (RPA). That formalism has an advantage to reveal the interaction effects in a simple way.…”
Section: Sws In Fermion-boson Mixturesmentioning
confidence: 99%
“…In Ref. [44] it was shown that RPA cannot recover the SWS, hence an alternative one is necessary. In this section we shall take into account the contribution from a two-phonon process, and compare the diagrammatic calculations with the numerically exact path integral QMC results [51].…”
Section: Vertex Correction and The Swsmentioning
confidence: 99%
See 3 more Smart Citations